G. Clinton Gardner papers - Gardner, G. Clinton (George Clinton), 1834-1904.
Letters written to family members in Washington, D.C., by Gardner as a member of the United States and Mexican Boundary Survey surveying the Mexican boundary, 1849-1852, and Northwest Boundary Commission surveying the northwest Canadian boundary, 1858-1859.
Civil engineer and railroad executive.
Collection material in English.
Keywords: Gardner family -- Correspondence; Northwest Boundary Commission, 1857-1869.; United States and Mexican Boundary Survey; Northwest boundary of the United States; Canada -- Boundaries -- United States; Mexico -- Boundaries -- United States; United States -- Boundaries -- Canada; United States -- Boundaries -- Mexico; Civil engineers; Executives